Comprehensive account of Leucophellinus hobsonii (Berk. ex Cooke) Ryvarden (Schizoporaceae) a poroid species from Ratnagiri district of Western Ghats of India - Yemul, N.B.; Kanade, M.B.; Murumkar, C.V. (Indian Forester, 2019)
Western Ghats of India is one of the world's 35 biodiversity hotspots and is rich in mycobiota. The field surveys were conducted in the monsoon season of 2016 in the tropical moist deciduous forest of Ratnagiri district of India to collect wood rotting poroid fungi. Total 127 specimens collected, of which one specimen is identified as Leucophellinus hobsonii (Berk. ex Cooke). It was reported from Bombay, India in 1879 by Berkeley and named by M. C. Cooke as Polyporus hobsonii Berk. ex Cooke, 1886. This specimen was revaluated by Ryvarden in 1988 at Kew herbarium and renamed it as Leucophellinus hobsonii. As one of the specimens collected by us is also found to be L. hobsonii, we were curious to know its morphological and cytological details. Therefore we have carried out a comprehensive study on L. hobsonii from Ratnagiri district of Western Ghats of India. The basidiocarp of this species is pileate, sessile and imbricate. Pileal surface is cream coloured. Pores are angular to labyrinthine. Hyphal system is monomitic, basidia clavate, cystidia present and basidiospores broadly ellipsoid.